New Normal Attribute Destination Image as Strategy for Tourism Recovery After COVID-19 - Taufik, Nuryanti; Santosa, Allicia Deana (Journal of Indonesian Tourism, Hospitality and Recreation, 2022)
ABSTRACTThe purpose of this research is to analyze changing behavior of tourists as an effect of the COVID-19 pandemic. One of the changes in tourist behavior during the COVID-19 pandemic is how tourists perceive the image of a tourist destination they visit during the pandemic. This study will explore more deeply changes in tourist perceptions of the new normal attribute destination image by adding a health protocol implementation dimension as a new dimension in measuring attribute destination image. The survey was conducted on 163 tourists who had already made tourist visits in new normal conditions. To determine the dimensions and measurements of the attribute destination image in new normal conditions, this research data analysis technique uses Confirmatory Factor Analysis (CFA). The results of the study found that the health protocol implementation dimension was able to be part of the measurement of the new normal attribute destination image. Based on the results of this study, every tourist destination needs to consider health protocol implementation so that it can begin to adapt to changing tourist behavior as a result of the impact of the COVID-19 pandemic.ABSTRAKTujuan dari penelitian ini adalah untuk menganalisis perubahan perilaku wisatawan sebagai dampak dari pandemi COVID-19. Salah satu perubahan perilaku wisatawan selama pandemi COVID-19 adalah bagaimana wisatawan memandang citra destinasi wisata yang mereka kunjungi selama pandemi. Penelitian ini akan menggali lebih dalam tentang perubahan persepsi wisatawan terhadap citra destinasi atribut new normal dengan menambahkan dimensi implementasi protokol kesehatan sebagai dimensi baru dalam pengukuran citra atribut destinasi. Survei dilakukan terhadap 163 wisatawan yang sudah melakukan kunjungan wisata dalam kondisi normal baru. Untuk mengetahui dimensi dan pengukuran atribut citra tujuan pada kondisi new normal, teknik analisis data penelitian ini menggunakan Confirmatory Factor Analysis (CFA). Hasil penelitian menemukan bahwa dimensi implementasi protokol kesehatan mampu menjadi bagian dari pengukuran citra tujuan atribut new normal. Berdasarkan hasil penelitian ini, setiap destinasi wisata perlu memperhatikan penerapan protokol kesehatan agar dapat mulai beradaptasi dengan perubahan perilaku wisatawan akibat dampak pandemi COVID-19.